The ultrasound and light combination as a new approach for BODIPY dyes with the enhanced singlet oxygen formation - Karanlik, Ceren Can; Erdogmus, Ali (ELSEVIER SCIENCE SA, 2024)
Sonophotodynamic Therapy (SPDT) is a new approach that uses the light of photodynamic therapy (PDT) and ultrasound of sonodynamic therapy (SDT) together. Although it is known that singlet oxygen production in phthalocyanine-derived photosensitizers increases significantly with the use of the SPDT method, there is no study in the literature investigating the singlet oxygen generating capacity of BODIPY (4,4-difluoro-4-bora-3a,4a-diaza-s-indacene) compounds with the SPDT method. This study was motivated by the desire to evaluate the singlet oxygen production capacity of BODIPY compounds by using SPDT method. For this reason, in this study, we present the synthesis of novel BODIPY derivative with meso-dibenzothienyl segment, diiodine moieties at 2-,6-positions and distyryl structure at 3-,5-positions. The resulting compound was illuminated by applying spectroscopic techniques including 1H-NMR, UV-Vis, MS and elemental analysis. This study aimed to demon-strate and compare the potentials of BODIPY compound in PDT and SPDT applications based on the photo-chemical and sonophotochemical measurements. While the calculated (D Delta value was 0.34 for BDPY4 after light irradiation, this value increased to 0.76 after combination of light and ultrasound irradiation used together. Based on the fact that the synthesized BDPY4 may be a suitable agent in SPDT applications, this study will be a precursor in understanding the sonophotochemical measurements of BODIPY compounds for in vivo or in vitro studies in the future.
Keywords: BODIPY; Sensitizer; Photodynamic therapy; Sonophotodynamic therapy; RECENT PROGRESS; PHOTOSENSITIZERS; CANCER; COMPLEXES; Chemistry